2017
DOI: 10.3389/fpsyg.2017.00015
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic Pleasure versus Aesthetic Interest: The Two Routes to Aesthetic Liking

Abstract: Although existing research has established that aesthetic pleasure and aesthetic interest are two distinct positive aesthetic responses, empirical research on aesthetic preferences usually considers only aesthetic liking to capture participants’ aesthetic response. This causes some fundamental contradictions in the literature; some studies find a positive relationship between easy-to-process stimulus characteristics and aesthetic liking, while others suggest a negative relationship. The present research addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
126
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(143 citation statements)
references
References 39 publications
15
126
2
Order By: Relevance
“…Our overarching prediction was that our aesthetic liking data would reveal the existence of an interaction between stimulus conceptual fluency and complexity given that high complexity stimuli should trigger more deliberative processing than low complexity stimuli, with such deliberative processing then engendering higher liking ratings at increasing levels of conceptual fluency. Our findings revealed the existence of this expected modulation of conceptual fluency by complexity in relation to aesthetic judgments of beauty, thereby attesting to the predictive strength of Graf and Landwehr's (2015) PIA Model (see also Graf & Landwehr, 2017). Put simply, we predicted and found that people like more complex abstract artworks compared to simpler ones, but only when they can fairly readily derive meaning from these apparently complex stimuli.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our overarching prediction was that our aesthetic liking data would reveal the existence of an interaction between stimulus conceptual fluency and complexity given that high complexity stimuli should trigger more deliberative processing than low complexity stimuli, with such deliberative processing then engendering higher liking ratings at increasing levels of conceptual fluency. Our findings revealed the existence of this expected modulation of conceptual fluency by complexity in relation to aesthetic judgments of beauty, thereby attesting to the predictive strength of Graf and Landwehr's (2015) PIA Model (see also Graf & Landwehr, 2017). Put simply, we predicted and found that people like more complex abstract artworks compared to simpler ones, but only when they can fairly readily derive meaning from these apparently complex stimuli.…”
Section: Discussionsupporting
confidence: 78%
“…That said, there are many important theoretical ideas and subtle distinctions that underpin Graf and Landwehr's theorising (see also Graf & Landwehr, 2017), which also render it somewhat distinct from other default-interventionist theories as well as the metareasoning framework. Although we do not wish to get sidetracked either into reviewing the full model or examining recent debates regarding its potential limitations (e.g., Consoli, 2017), we nevertheless wish to emphasise three key assumptions of the model that relate closely to the factors that we manipulated in the study we report below.…”
Section: The Dual-process Approach To Aesthetic Likingmentioning
confidence: 99%
“…This influx of neuroscientific data has fermented a revolution in our understanding of aesthetic appreciation, allowing us to go beyond a mere description of "stimuluspreference laws" and study the actual functional machinery involved in aesthetic appreciation (Skov, 2019a). This revolution has also paved the way for innovative behavioral studies investigating such mechanisms independent of stimulus properties (e.g., Brielmann & Pelli, 2017;Graf & Landwehr, 2017;Huang et al, 2018). In his pioneering book Vorschule der Ästhetik, Fechner suggested that aesthetic appreciation could be studied experimentally by scaling the magnitude of a sensory stimulus and relating individual stimulus properties to behavioral responses (Fechner, 1876).…”
Section: What Neuroscience Tells Us About Aesthetic Appreciationmentioning
confidence: 99%
“…This relatively simple one-word change in the experimental procedure was used to explore the potential impact of aha on preference and it lead to dramatic change in the pattern of preference ratings. Graf & Landwehr's (2017) work on art appreciation showed that reductions in disfluency, due to on-going processing, lead to greater ratings of interest. In the current studies, searching for a camouflaged object is a disfluent process but its identification reduces disfluency and, in agreement with Graf & Landwehr's (2017) findings, interest in camouflaged objects was greater than in non-camouflaged (immediately apparent) objects.…”
Section: Discussionmentioning
confidence: 99%
“…Graf & Landwehr's (2017) work on art appreciation showed that reductions in disfluency, due to on-going processing, lead to greater ratings of interest. In the current studies, searching for a camouflaged object is a disfluent process but its identification reduces disfluency and, in agreement with Graf & Landwehr's (2017) findings, interest in camouflaged objects was greater than in non-camouflaged (immediately apparent) objects. This difference in interest between camouflaged and noncamouflaged objects was even greater when the reaction time task was missing (Experiment 5) than when it was present (Experiment 4).…”
Section: Discussionmentioning
confidence: 99%